Uspešno poučevanje in učenje tehnike in tehnologije s konstrukcijskimi sestavljankami - Papotnik, Amand (Revija za elementarno izobraževanje, 2008)
Successful Teaching and Learning in the Subject Technics and Technology Using Construction Sets. The article deals with some detailed strategies for aquiring new knowledge with the help of the global-centered strategy of using construction sets. Special stress is given to the development of abilities which can be developed within the framework of chosen strategies. These strategies are especially suitable for cross-curricular subject planning, which allows pupils to connect to and realize the subject material, thus giving them a better grasp of the knowledge being learned. This process is supported by the constructivists, who are of the opinion that knowledge in its final form can neither be "given" to or "accepted" by somebody else, but should be built-up afresh using each individual's own thoughts and ideas.
Keywords: education; technique and technology; construction sets; skills